Small-Scale Biogas Reactors Converting Organic Waste to Energy and Ferlilizer: A Case Study of Sam Ratulangi University Green Campus Project - Ellen J. Kumaat; Indry S. Manembu; Susan M. Mambu; Glanny M. C. Mangindaan (Journal of Sustainability Perspectives, 2022)
Organic Waste Management (OWM) has been a major problem worldwide in most of the cities among developing countries such as Indonesia. Sam Ratulangi University (UNSRAT) is located in the rural setting of the medium city of Manado, North Sulawesi, Indonesia, was committed to achieving minimum waste across all campus locations, by averting some waste through reduced consumption and diverting the rest through recycling, composting, or reusing. A large amount of yard waste such as grass, leaves, and branches is produced on campus in UNSRAT, which is a problem that needs to be effectively solved. Composting is a sustainable OWM practice that converts organic waste into valuable products such as liquid organic fertilizer and biogas. OWM and bioenergy production are complementary to each other, because the application of compost back into the soil can contribute to sustainable soil health, and biogas is the principal renewable energy source that manages potentially harmful organic wastes. Thus, in the present article, recycling of organic waste has recently become an important topic and the intensification of organic waste conversion strategies was elaborated and analyzed frequently. The result indicated that creating a small-scale biogas reactor is more cost-effective, eco-friendly, and presents a sustainable waste treatment method within UNSRAT campus into valuable products that promote the university as a green campus. Keyword: bioenergy; biogas reactor; organic waste; organic liquid fertilizer